6+2x-1=9x+7-6x

Simple and best practice solution for 6+2x-1=9x+7-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+2x-1=9x+7-6x equation:


Simplifying
6 + 2x + -1 = 9x + 7 + -6x

Reorder the terms:
6 + -1 + 2x = 9x + 7 + -6x

Combine like terms: 6 + -1 = 5
5 + 2x = 9x + 7 + -6x

Reorder the terms:
5 + 2x = 7 + 9x + -6x

Combine like terms: 9x + -6x = 3x
5 + 2x = 7 + 3x

Solving
5 + 2x = 7 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
5 + 2x + -3x = 7 + 3x + -3x

Combine like terms: 2x + -3x = -1x
5 + -1x = 7 + 3x + -3x

Combine like terms: 3x + -3x = 0
5 + -1x = 7 + 0
5 + -1x = 7

Add '-5' to each side of the equation.
5 + -5 + -1x = 7 + -5

Combine like terms: 5 + -5 = 0
0 + -1x = 7 + -5
-1x = 7 + -5

Combine like terms: 7 + -5 = 2
-1x = 2

Divide each side by '-1'.
x = -2

Simplifying
x = -2

See similar equations:

| 3d+5+17= | | x(y+2)+y=1 | | 2(3x-1)=3x-2 | | x-x*0.1=500 | | 9y-9y^2-2=0 | | t-1.5=5 | | 7(x-1)-(x-4)=8x-1 | | 4+1/4+0.75=x | | (2x+9)+(-3x+9)= | | 25x^3-4x^2-150x+150=0 | | 5x+7-3x-2=4x-1 | | 5x*7-3x-2=4x-1 | | 8x^2+14x-5=0 | | X-(360-x)=124 | | 48=9W-W | | X+10.4=12.2 | | H-18=11 | | 6x+36=3x+76 | | z^2+(z+3)i+1=0 | | e^3-5x=531 | | 2x^3+3x^2+20=0 | | (m-5)(5m+3)=0 | | X^2-10x-3=-12 | | ln(y)=2x+5 | | (5x-3)+log(4)*(9-x)=3 | | (16x^2+36)= | | v=-3i | | (x-(0.21x))0.25=555.56 | | 0.1x-x=500 | | (x-(0.21x))0.25=500 | | 6r+7=22 | | 9x+7x-4x-5=55 |

Equations solver categories